Efeito do uso de agentes reticuladores de colágeno em procedimentos adesivos: estudos in vitro e in situ - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2015)
This study evaluated the effect of application of collagen cross-link agents under time and clinically relevant strategy, through two in vitro and one in situ studies. For in vitro experiment 1, 52 third human molars had exposed the dentin surface, acid etched and distributed according the 8 experimental groups: collagen cross-link agent (6.5% pronthocyanidin [PA], 0.1% UVA-light actived riboflavin [RB], 5% glutaraldehyde [GA] and distilled water as control group [CT], and 2 simplified etch-and-rinse systems (Adper Single Bond Plus [SB] and Tetric N-Bond [TN]. The cross-link agentes were activelly applied for 60 s, bonded and restorated with composite resin. Then, the teeth were sectioned to obtain specimens and tested in immediately [IM] and after 6 months [6M] storage time for microtensile bond strength (μTBS) and nanoleakage (NL), and IM for degree of conversion (DC) and MMP-activity within the hybrid layer. Additional 24 teeth were used by cytotoxicity assay. For in vitro experiment 2, 2 etchant agentes were tested (2%PA with 10% phosphoric acid [ACPA] and 35% phosphoric acid [CT]). Dentin of 16 teeth was exposed, etched, bonded using SB adhesive, and restored with composit resin. These teeth were tested by μTBS, NL in IM and 6M; and MMP-activity within the hybrid layer. Additional 10 teeth had flated the enamel surfaces and tested by enamel bond strength in IM and 6M. For the in situ experiment 3, 40 teeth were used, in which 2 cavities prepared. These cavities were etched, treated according the experiment 1, bonded and restored with composite resin. One restoration for each tooth was tested IM and another was included in a palatal device in cariogenic oral environment [COE] for 10 volunteers during 14 days. The restorations were sectioned and tested by microhardness, μTBS, NL and morphology of the hybrid layer for differential staining technique. All the data were analyzed by 2 way-ANOVA and Tukey’s test (α = 0.05). For experimente 1, all the collagen cross-link agentes were effective to reduce the resin-dentin degradation after 18M e did not exhibit cytotoxic potential, except the GA (p<0.05). For the experiment 2, the PA containing in etchant reduced the resindentin bond degradation (p<0.05) and did not affect the resin-enamel bond strentgh (p>0.05). However for in situ experiment 3, only the PA and GA reduced the resin-dentin degradation (p<0.05) in COE. The collagen cross-link agentes were effective to reduce the resin-dentin degradation, in time and relevant clinically strategy. The GA exhibited cytotoxic potential and should be avoided for clinical use.
Keywords: colágeno dental; proantocianidina; riboflavina; glutaraldeído; adesão dental; dentin collagen; proanthocyanidin; riboflavin; glutaraldehyde; dental bonding; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA